Waterlily as a Creation Idea of Leather Artwork Panel Work - Akhra, Safa San; Marwoto, Otok Herum; Wicaksono, Agung (Institut Seni Indonesia Yogyakarta, 2022)
Application of Resin Coating Techniques to Leather Craft Works with the Ideaof Creation of Waterlily Plants is an individual idea inspired by the waterlily, a type of aquatic ornamental plant with beautiful and positive philosophical meaning and value. Inspired by the empirical gardening experience, the inspiration was based on interest in the uniqueness of the waterlily in a pond. The final project aimed to create panel work made of plant-based leather with as a creative concept. In the work creation, the approach method used was Monroe Beardsley's aesthetic with three elements: unity, complexity and intensity. The creationmethod used was SP. Gustami's creation method with 3 (three) stages and 6 (steps). The creation techniques used were knitting, cutting, pasting, sewing, and forming. The work creation achievement was leather artwork panel work by visualizing a waterlily as the reference object. In the work creation, resin additives as an adhesive and a skin coating were added as the work's aesthetic value. The final project focused on the aesthetic function of a decorative object.